CLASSIFICATION OF LEXICAL STYLISTIC DEVICES - Sulaymonov Samariddin; Iskandarov Hayotbek; Abdurakhmanova Zilola (Ta’lim innovatsiyasi va integratsiyasi, 2023)
Annotatsiya Lexical stylistic device is such type of denoting phenomena that serves to create additional expressive, evaluative, subjective connotations. In fact we deal with the intended substitution of the existing names approved by long usage and fixed in dictionaries, prompted by the speaker’s subjective original view and evaluation of things. Each type of intended substitution results in a stylistic device called also a trope as well.